Diseño e implementación de un sistema de desalinización a pequeña escala alimentado por medio de un sistema solar fotovoltaico (2020)
This document presents the design of a desalination plant with energy supplied by an array of photovoltaic solar panels. The corresponding calculations are made to select each of the system components in detail. Additionally, a respective cost analysis is presented.--Taken from the Degree Document Format.